Effects of Chromium and Copper on the Growth of Monascus purpureus - Mangar, Vishw (2017)
Heavy metals including copper (Cu) and chromium (Cr) have higher density than water. Recently, with rapid industrialization there has been an exponential increase in their use that has resulted in heavy metal pollution. Unlike other types of pollution, heavy metals are not bio-degradable and therefore, persist in the environment and cause serious detrimental effects on the ecosystem. Bio-accumulation in food chain has dramatically increase their exposure in man. Heavy metals cause serious health problems at even very low levels. For instance, Cr and Cu cause several organ damage, genetic diseases and cancers. Therefore, soil and water contaminated with heavy metals necessitate immediate remediation. Amongst the methods used, bioremediation particularly mycoremediation is both eco-friendly and less costly. Therefore, the identification of these putative fungi for mycoremediation is highly significant and promising. Till date, there is no report on Monascus purpureus being studied for bioremedial properties. Therefore, the purpose of this research was to determine the effects of different concentration of Cu and Cr on the growth of M. purpureus. Ten different concentrations of Cu and Cr solution (0, 1, 5, 10, 20, 40, 80, 120, 160, 200 mg/mL) were used for the growth of the fungi. Growth of mycelium was monitored for a period of 10 days. Rate of growth was measured by radial growth of M. purpureus. The data was statically analyzed by performing one-way ANOVA. M. purpureus was able to grow in concentrations of up to 120 mg/L of Cu and Cr. The negative control had the highest average growth rate with 4.63 mm/d. The presence of Cu and Cr in the culture media caused a decrease in growth rate from 4.63 mm/d (negative control) to 0 mm/d in PDA media supplemented with 160 and 200 mg/L (both in Cu and Cr). The lowest growth rate for both Cu and Cr (in the single inoculation) was observed at a concentration of 80 mg/L with 3.10 mm/d and 2.80 mm/d for Cu and Cr respectively. In addition, the lower growth rate in medium containing Cr indicated that Cr might be more toxic. The highest growth rate in Cu containing medium was 4.60 mm/d at concentration of 120 mg/L whereas that of Cr was 4.0 mm/d at a concentration of 10 mg/L. In the double inoculation, the highest growth rate obtained in both Cu and Cr containing media was 3.8 mm/d at the same concentration of 10 mg/L. The highest concentration of Cu and Cr that sustain growth was 120 mg/L and that inhibited growth was 160 and 200 mg/L. This study was done with a view to investigate if the fungi can be a putative bioremediator of heavy metal. This is because for the fungi to be able to remediate those heavy metal it should be able to survive in the presence of these heavy metal. As M. purpureus grew on concentrations of Cr and Cu of up to 120 mg/L, it could play an important role in bioremediation. Therefore, further research need to be done to determine its potential role in mycoremediation of Cu, Cr and other heavy metals.